PERAN KOMITMEN ORGANISASI SEBAGAI MEDIASI PENGARUH KEPEMIMPINAN TERHADAP KINERJA - Sutra Dewi; Dedy Takdir Syaifuddin; La Ode Bahana Adam (Pascasarjana Universitas Halu Oleo, 2019)
The purpose of this study was to examine and explain the role of organizational commitment as a mediation of the influence of leadership on employee performance in the Southeast Sulawesi Province Food Security Service. Approach this research is survey with design explanatory research. Data collection is carried out in a cross-section with use instrument in the form of questionnaire. Population research this is all over Employee on Southeast Sulawesi Province Food Security Service as many as 70 people except leader (head service) and researcher alone . Equipment The analysis for testing hypothesis is Partial least square (PLS). The results showed that leadership had a positive and significant effect on organizational commitment, organizational commitment was positive and significant influence on employee performance, leadership had a positive and not significant effect on employee performance, organizational commitment served as a mediation of the influence of leadership on employee performance.Keywords: leadership, organizational commitment, employee performance